Modeling answer constraints in constraint logic programs - Gabbrielli, Maurizio; Levi, Giorgio 1942- (1991)
Abstract: "The constraint logic programming paradigm CLP (X) (CLP for short) has been proposed by Jaffar and Lassez in order to integrate a generic computational mechanism based on constraints with the logic programming framework. This paradigm retains the semantic properties of logic languages, namely the existence of equivalent operational, model theoretic and fixpoint semantics. Moreover, since computation is performed over the particular domain of computation X, CLP (X) programs have an equivalent 'algebraic' semantics, i.e. a semantics which is defined directly on the algebraic structure of the domain X. In this paper we propose an extension of such a semantics, for the success set case, in order to fully characterize the operational behaviour of programs
Keywords: Logic programming